The Informer [videorecording (DVD)] - Ford, John, 1894-1973; Nichols, Dudley, 1895-1960; McLaglen, Victor, 1886-1959; Angel, Heather, 1909-1986; Foster, Preston, 1900-1970; Grahame, Margot, 1911-1982; Ford, Wallace, 1898-1966; O'Connor, Una, 1880-1959; Kerrigan, J. M. (Joseph M.), 1884-1964; Sawyer, Joseph, 1906-1982; Fitzgerald, Neil, 1892-1982; Meek, Donald, 1878-1946; et al. (John Ford film collection., 2006)
The scene is Dublin, 1922. Gypo Nolan stumbles through a foggy Irish night, his brain pickled in whiskey and his soul tormented by shame and fear. Gypo is an informer, a turncoat who betrayed his friend to the British police for 20 pounds. Now he can't spend the money fast enough, nor can he run from his treachery fast enough as he brawls, brags, swaggers and lies his way toward his fate.